A survey of hospital toilet facilities. Issue 6831 (4th April 1992) - Travers, A. F.; Burns, E.; Penn, N. D.; Mitchell, S. C.; Mulley, G. P.
Abstract : OBJECTIVE--To assess the quality of toilet facilities available for disabled people in a large provincial teaching hospital. DESIGN--Survey of toilet facilities for patients on the wards and in the outpatient department. SETTING--Teaching hospital in Leeds. RESULTS--Although the quality of toilet facilities varied, none met the standards recommended by the British Standards Institution. The worst facilities were found on a ward accommodating elderly patients, where the toilets were unsuitable for use by disabled people and bedside commodes had to be used instead. CONCLUSION--Toilet provision within a major hospital failed to meet standards required for disabled people. Admission to hospital may therefore result in loss of independence and dignity. If hospitals are to be centres of excellence, greater consideration must be given to the requirements of disabled people in the design of new wards, and current inadequate facilities should be upgraded.